Influenza Vaccination and Risk of Stroke in Women With Chronic Obstructive Pulmonary Disease: A Nationwide, Population-Based, Propensity-Matched Cohort Study - Chen, Chun-Chao; Lin, Cheng-Hsin; Chiu, Chun-Chih; Yang, Tsung Yeh; Hsu, Min-Huei; Wang, Yuan-Hung; Lei, Meng-Huan; Yeh, Hsien Tang; Fang, Yu-Ann; Hao, Wen-Rui; Liu, Ju-Chi (Frontiers in Medicine, 2022)
Backgrounds The risk of stroke is higher among patients with chronic obstructive pulmonary disease (COPD) than among the healthy population. Moreover, women generally have worse long-term stroke outcomes than men. Methods The data of 6681 women with COPD (aged ≥ 65 years) registered in Taiwan’s National Health Insurance Research Database were retrospectively analyzed from January 1, 2001 to December 31, 2011. After 1:1 propensity score matching, the patients were divided into vaccinated and unvaccinated groups. Results In total, 5102 women were enrolled. The vaccinated group had a significantly lower risk of total, hemorrhagic, and ischemic stroke than the unvaccinated group (adjusted hazard ratio [aHR]: 0.60, 95% confidence interval [CI]: 0.54–0.67; aHR: 0.59, 95% CI: 0.43–0.83; and aHR: 0.59, 95% CI: 0.52–0.68, respectively). A lower risk of stroke was observed among the women aged 65–74 and ≥75 years, and the association was dose-dependent in all types of stroke (aHR: 1.08, 95% CI: 0.92–1.26; aHR: 0.70, 95% CI: 0.60–0.82; and aHR: 0.32, 95% CI: 0.26–0.38 for those vaccinated 1, 2 to 3, and ≥4 times, respectively, during the follow-up period). Women with a CHA2DS2-VASc score (conditions and characteristics included congestive heart failure, hypertension, diabetes, stroke, vascular disease, age, and sex) of 2–3 and ≥4 had a significantly lower risk of ischemic stroke while receiving more vaccinations. A smaller significant lower risk of hemorrhagic stroke after more than 4 times of vaccination was noted in the women with a CHA2DS2-VASc score of ≥4. Both interrupted and non-interrupted vaccination was associated with lower risk of stroke occurrence. Conclusion Influenza vaccination is associated with a lower risk of total, hemorrhagic, and ischemic stroke among women with COPD, and the association is dose-dependent. However, the findings may be limited by unmeasurable confounders. Further investigations on this subject are warranted.